2012
DOI: 10.1007/s00276-012-0947-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy of the human middle ear: an insight into cochlear implant surgery

Abstract: Microscopic anatomical studies of the temporal bone are essential to safely perform surgical intervention within the middle ear. The results shows that morphometric data concerning different anatomical structures inside the middle ear, particularly distances, is an important contribution towards the planning of safe surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Thanks to its important integrative function, present-day research for middle ear structure was reported for several species such as the chinese bamboo rat (Pleštilová, Hrouzková, Burda, & Šumbera, 2016), toad (Womack, Stynoski, Voyles, Coloma, & Hoke, 2018), rabbit (Guan et al, 2019), pig (Pracy, White, Mustafa, Smith, & Perry, 1998), miniature pigs (HaiJin et al, 2013), humans, (Arechvo et al, 2013;Isaacson, 2014;Luers & Hüttenbrink, 2016;Sawada, Nara, Fukui, Dodo, & Hirata, 2014;Stieger, Djeric, Kompis, Remonda, & Häusler, 2006;Whyte et al, 2001) other primates, moles (Mason, 2006), dog (Berghes, Parvu, Cucoanes, & Cuca, 2010;Ortug & Türkmenoğlu, 2005), Indian mangoose (Kamali, Gholami, Ahrari-Khafi, Rasouli, & Shayegh, 2015), horse, cat, cow, rat, mouse (Amin & Tucker, 2006;Blanke, Aupperle, Seeger, Kubick, & Schusser, 2015;Botti, Secci, Ragionieri, Dessole, & Acone, 2006;Mohammadpour, 2010) or other extinct rodents (Lange, Stalleicken, & Burda, 2004), hamster, gerbil, New Zeeland rabbit (Kurtul, Cevik, Bozkurt, & Dursun, 2003), ostrich (Beșoluk et al, 2019;Keenan, Mears, & Skedros, 2017), degu (Argyle & Mason, 2008), weasel or chinchilla (Bergin, Vlajkovic, Bird, & Thorne, 2013;Carrasco, Maass, Dentone, Miranda, & Kukuljan, 2008;Charuta et al, 2011;Hoffstetter et al, 2011;Maier, Tröscher, & Ruf, 2018;Maravilla et al, 2011;Martonos et al, 2019;Rodrigues, Shinohara, Andreo, Buchaim, & Ahmed, 2012;…”
mentioning
confidence: 99%
“…Thanks to its important integrative function, present-day research for middle ear structure was reported for several species such as the chinese bamboo rat (Pleštilová, Hrouzková, Burda, & Šumbera, 2016), toad (Womack, Stynoski, Voyles, Coloma, & Hoke, 2018), rabbit (Guan et al, 2019), pig (Pracy, White, Mustafa, Smith, & Perry, 1998), miniature pigs (HaiJin et al, 2013), humans, (Arechvo et al, 2013;Isaacson, 2014;Luers & Hüttenbrink, 2016;Sawada, Nara, Fukui, Dodo, & Hirata, 2014;Stieger, Djeric, Kompis, Remonda, & Häusler, 2006;Whyte et al, 2001) other primates, moles (Mason, 2006), dog (Berghes, Parvu, Cucoanes, & Cuca, 2010;Ortug & Türkmenoğlu, 2005), Indian mangoose (Kamali, Gholami, Ahrari-Khafi, Rasouli, & Shayegh, 2015), horse, cat, cow, rat, mouse (Amin & Tucker, 2006;Blanke, Aupperle, Seeger, Kubick, & Schusser, 2015;Botti, Secci, Ragionieri, Dessole, & Acone, 2006;Mohammadpour, 2010) or other extinct rodents (Lange, Stalleicken, & Burda, 2004), hamster, gerbil, New Zeeland rabbit (Kurtul, Cevik, Bozkurt, & Dursun, 2003), ostrich (Beșoluk et al, 2019;Keenan, Mears, & Skedros, 2017), degu (Argyle & Mason, 2008), weasel or chinchilla (Bergin, Vlajkovic, Bird, & Thorne, 2013;Carrasco, Maass, Dentone, Miranda, & Kukuljan, 2008;Charuta et al, 2011;Hoffstetter et al, 2011;Maier, Tröscher, & Ruf, 2018;Maravilla et al, 2011;Martonos et al, 2019;Rodrigues, Shinohara, Andreo, Buchaim, & Ahmed, 2012;…”
mentioning
confidence: 99%
“…Measurements were conducted with DinoCapture 2.0 software as in other series, with 2 authors meeting and mutually agreeing on distances. 11…”
Section: Methodsmentioning
confidence: 99%
“…Measurements were conducted with DinoCapture 2.0 software as in other series, with 2 authors meeting and mutually agreeing on distances. 11 The following were determined for each temporal bone: presence or absence of a complete (plate) Korner's septum in the mastoid cavity, the distance from the inferior aspect of the PsS to the tegmen tympani, the shortest distance from the PsS to the posterior body of the incus, the greatest distance from the posterior prominence of the PsS to the posterior body of the incus, and the distance from the PsS to the incus buttress. The mean distance as for each measurement are reported ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation